The Effect of Live Streaming, Discounts, and Shopping Lifestyle on Impulse Buying in Cosmetics on Tiktok Shop - Kurnaesih Safitri; Silvy Ahwattun Khasanah; May Dedu (Journal of World Science, 2025)
The rapid growth of Indonesia’s cosmetics industry, fueled by digital transformation and social commerce, has made impulse buying a critical phenomenon. This study analyzes the effects of Live Streaming, Discounts, and Shopping Lifestyle on Impulse Buying in TikTok Shop, a platform dominating Indonesia’s e-commerce landscape. Using a quantitative approach, data from 145 TikTok Shop users in Cirebon Regency were analyzed via multiple linear regression. Results confirmed all three variables significantly influence impulse buying, with Shopping Lifestyle (? = 0.362, *p* = 0.000) as the strongest predictor, followed by Live Streaming (? = 0.385, *p* = 0.000) and Discounts (? = 0.193, *p* = 0.012). The model explained 66.5% of variance, underscoring their collective impact. Findings align with prior research but extend knowledge by focusing on TikTok Shop’s unique ecosystem. Practical implications suggest businesses should prioritize live streaming interactions, time-sensitive discounts, and hedonistic lifestyle targeting. Limitations include unexamined variables (e.g., social influence), urging future research to expand the model. This study bridges theoretical and practical gaps in digital consumer behavior, offering actionable insights for marketers in the social commerce era.